2010
DOI: 10.1007/s00439-010-0891-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of a haplotype in the AKT1 gene associated with glucose homeostasis and metabolic syndrome

Abstract: A small 12-kb haplotype upstream of the AKT1 gene has been found to be associated with insulin resistance phenotypes. We sought to define the functional consequences of the three component polymorphic loci (rs1130214, rs10141867, rs33925946) on AKT1 and the upstream ZBTB42 gene. 5′ RACE analysis of AKT1 transcripts in human skeletal muscle biopsies showed the predominant promoter to be 2.5 kb upstream of exon 2, and distinct from those promoters previously reported in rat. We then studied the effect of each of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
(48 reference statements)
1
11
0
Order By: Relevance
“…In the current study, variant genotype and allele of rs1130214 was related to increased risk of OSCC, which was in accordance with the findings in non‐small cell lung cancer and prostate cancer in previous studies . Despite human cancer, polymorphism rs1130214 was also found to contribute to glucose/obesity‐related metabolism disturbance , Parkinson's disease , and schizophrenia , implying rs1130214 might be an important functional SNP with a major impact on various human diseases. In addition, patients with variant genotypes and allele of rs3803300 also had a higher risk of OSCC.…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, variant genotype and allele of rs1130214 was related to increased risk of OSCC, which was in accordance with the findings in non‐small cell lung cancer and prostate cancer in previous studies . Despite human cancer, polymorphism rs1130214 was also found to contribute to glucose/obesity‐related metabolism disturbance , Parkinson's disease , and schizophrenia , implying rs1130214 might be an important functional SNP with a major impact on various human diseases. In addition, patients with variant genotypes and allele of rs3803300 also had a higher risk of OSCC.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the G205T polymorphism may have a functional effect (Thiselton et al 2008). Recently, Harmon et al (2010) reported that the T allele was part of an AKT1 haplotype that resulted in enhanced transcription in muscle and decreased transcription in fat. In keeping with these findings, we found that several obesity‐related metabolic variables differed prior to exercise training by the AKT1 G205T genotype in generally healthy, older men.…”
Section: Discussionmentioning
confidence: 99%
“…Although speculative, sex‐specific physiological differences in hormone levels or body composition may influence AKT1 genotype associations with obesity‐related metabolic variables. This is an interesting avenue for further research, since AKT1 variants appear to have tissue‐specific effects (Harmon et al 2010). In contrast, in the present study, these sex differences may be due in part to a statistical power issue resulting from the inclusion of HRT usage in the analyses involving women.…”
Section: Discussionmentioning
confidence: 99%
“…McKenzie et al (2011) studied the impact of the AKT1 G205T (rs1130214) polymorphism on these physiological parameters and the response to exercise training. The G205T single nucleotide polymorphism is not in a protein‐coding region, and it has recently been shown to have a cell‐type‐specific impact on transcriptional activity (Harmon et al 2010). In particular, the T allele appears to enhance transcription in muscle cells, while inhibiting transcription in adipocytes (Harmon et al 2010), albeit the human sequence studied in murine cells.…”
mentioning
confidence: 99%
“…The G205T single nucleotide polymorphism is not in a protein‐coding region, and it has recently been shown to have a cell‐type‐specific impact on transcriptional activity (Harmon et al 2010). In particular, the T allele appears to enhance transcription in muscle cells, while inhibiting transcription in adipocytes (Harmon et al 2010), albeit the human sequence studied in murine cells. Thus, it could be expected that McKenzie et al (2011) would find a complex in vivo phenotype for the AKT1 G205T (rs1130214) polymorphism.…”
mentioning
confidence: 99%